Comparison between peritoneal dialysis and hemodialysis on kidney function recovery in incident kidney failure: A nationwide cohort study. Issue 3 (13th January 2022) - Kuo, George; Chen, Jia‐Jin; Cheng, Ya‐Lien; Fan, Pei‐Chun; Lee, Cheng‐Chia; Chang, Chih‐Hsiang
Abstract: Background: Patients with kidney failure who start dialysis have a chance of kidney function recovery. Whether the initial dialysis modality affects the possibility of recovery is not fully understood. Methods: We included patients diagnosed with kidney failure requiring dialysis during 2001–2013 from the Taiwan National Health Insurance Research Database. We excluded diabetic and elderly patients. Kidney function recovery was defined as not receiving dialysis therapy for longer than 3 months. The primary outcome was kidney function recovery, and the secondary outcome was all‐cause mortality during a 3‐year follow up. Results: A total of 12, 619 patients was eligible for analysis, with 981 received PD and 11, 638 received HD. Total 620 patients had kidney function recovery during a 3‐year follow up, which represented 4.9% of the entire cohort. After propensity score matching, the PD groups were more likely to experience kidney function recovery (subdistribution hazard ratio [SHR]: 1.64, 95% confidence interval [CI]: 1.19–2.25). The risk of all‐cause mortality between groups did not significantly differ (hazard ratio [HR]: 1.23, 95% CI: 0.89–1.70). Conclusion: The study found that in nonelderly, nondiabetic patients who received inadequate predialysis nephrology care before kidney failure, PD is associated with a higher chance of kidney function recovery.